The Only Woman in the Room : Golda Meir and Her Path to Power - Lahav, Pnina (New Jersey Princeton University Press, 2022)
"One of the founders of the state of Israel, Golda Meir (1898-1978) was Israel's ambassador to the USSR in 1948-49, subsequently served as Israel's Minister of Labor and Foreign Minister, and in 1969 became Israel's fourth Prime Minister. Born to poor and uneducated parents in Kiev as Golda Mabovitz and raised in Milwaukee, she settled in the British Mandate of Palestine in 1917. American Jews of an older generation cherish memories of her as an affable, grandmotherly head of state, a mesmerizing speech maker, a tough negotiator with the likes of Nixon and Kissinger, and as a sort of mother of the Jewish people. However, public memory of her is much more equivocal in Israel, partly due to misogynistic strains in Israeli political culture and to her perceived failures as Prime Minister during the 1973 Yom Kippur War, the conflict that arguably led to her resignation and withdrawal from politics. This biography of Golda Meir explores the evolution of her political persona from her teenage years until her death, focusing in particular on her ever-recurring role as the only woman in a room full of male political actors. Pnina Lahav reexamines the story of Golda Meir's early passion for socialist Zionism, her decision to marry early, her separation from husband Morris Meyerson, her decision to leave her children in the care of others in order to pursue her political ambitions, and her conduct first in the Israeli cabinet and then as the country's Prime Minister. Often derided and humiliated by the men with whom she had to work, Golda Meir had her own complicated issues with gender and showed clear signs of having internalized the masculine ideals of the twentieth-century Zionist leadership (as when, for example, she derided her colleague and fellow cabinet minister Abba Eban, a cultivated, highly-educated man, as "effeminate"). And like another notable twentieth-century female political leader, Margaret Thatcher, she was less than supportive of younger women who wanted to follow in her footsteps. While Golda Meir has been the subject of several biographies, Lahav's is unique in its exploration of Golda's complicated and evolving relationship to her identity as a woman, particularly one who ascended to the apex of a patriarchal power structure"-- Provided by publisher
Include Illustration and Index
Keywords: Women prime ministers -- Israel -- Meir, Golda, 1898-1978